The Potential of integrating PV in the Heritage Sites Case Study of Dubai Museum - Faraj, Anwer Hadi (2015)
The conserved historic building presents a realistic and live scene of the past telling how the society has contributed in the development of the human civilization. The renovation work is complicated due to the lack of both expertise and active tailored solutions and undeveloped construction methods; it becomes more complicated when new technologies are intended to be integrated into the historical buildings. The contradiction between the old fashion scene of the historic building and the contemporary appearance of the renewable energy systems (e.g. PV panels) is the main challenge for architects and designers to integrate these systems into such buildings. This research aims to investigate the potential of integrating the PV panels in the heritage buildings (taking Dubai museum as a case study) considering the impact of the PV panels on the aesthetic characteristics of the building and the environmental benefits from the reduction of annual energy consumption by utilizing the PV system to generate and feed the building with clean and eco-friendly energy. Various integration configurations have been proposed and the power generation of each one has been calculated using the Integrated Environmental Solutions - Virtual Environment (IES-VE) software. The 3D visual models of 3 configurations that annually produce the highest power amount (21.7MWh, 9.53MWh and 3.81MWh) have utilized for on-site and online surveys to explore public acceptance about the visual impact of these proposals on the historical scene of the building. The surveys found that the proposals are in harmony with the places where to be installed and the public acceptance is significantly correlated with their awareness about the environment impact of utilizing the solar energy. In general, the idea of this study is applicable as per 93% of the participant’s feedback. The face-to-face interview with three heritage buildings specialists reveals that there are local and international obstacles prevent the adoption of the proposed concept. Locally, the building regulations prohibit integrate any additional features within the historical building and internationally, the UNESCO roles are very restricted in this regards as the fort is accredited as one of the world heritage sites. It was concluded that applying these three configurations will cover about 65% of the annual building’s energy demand and reduce the CO2 emission about 66.7%.